Governance and Development of Halal Industrial Infrastructure: Supporting the Pillars of Economic Sustainability - R, Wardatul Wahidah.; Siradjuddin; Andi Sulfati (PT FORMOSA CENDEKIA GLOBAL, 2024)
The halal industry refers to the economic sector that produces, markets and provides products and services that comply with Islamic halal principles. Halal products are products that are permitted to be consumed or used by Muslims in accordance with the teachings of the Islamic religion. The halal industry covers a wide range of sectors, including food and beverage, pharmaceuticals, cosmetics, finance, tourism and fashion. The halal industry has grown rapidly in recent decades in response to global demand for halal products. This research investigates the key pillars and infrastructure that support the halal industry, as well as their important role in ensuring the growth and sustainability of this sector. With these pillars and infrastructure, the halal industry can continue to develop and provide significant benefits to the economy and society at large. Through analysis of literature and secondary data. The findings show that with full support for these pillars and infrastructure, the halal industry can continue to grow sustainably, providing significant economic and social benefits, and meeting global consumers' needs for quality and trusted halal products. Implications of this research for public policy, industry practitioners, and researchers are also discussed.